Developing an Instrument to Measure the Effectiveness of the Link and Match Learning and the Availability of the Practical Laboratory Facilities on the Quality of Vocational School Graduates - Nurul Anriani; Muhammad Ibra Gholobi (Jurnal Pendidikan Indonesia Gemilang, 2024)
This study aimed to develop an appropriate standard instrument that can measure the influence of link and match learning and the availability of practical laboratory facilities on the quality of vocational school graduates. This instrument was prepared because no standard instrument based on this activity would theoretically improve the quality of vocational school graduates. The quality of graduates from an educational institution, including vocational schools, is influenced, among other things, by the competence of teachers, students, materials, methods, facilities and infrastructure, educational environment, curriculum, and costs. This research used a quantitative approach using survey research model with Structural Equation Modeling (SEM) analysis techniques. Factor analysis in this research used Confirmatory Factor Analysis (CFA) with the help of Lisrel 8.80 full version. The measurement model is based on Goodness of Fit criteria, namely, to test the suitability of the theoretical model with empirical data. The instrument is valid to measure the influence of link and match learning and the availability of practical laboratory facilities on the quality of vocational school graduates.